Endometrioid endometrial adenocarcinoma in a premenopausal woman with multiple organ metastases - Srikantia Nirmala; Rekha B; Rajeev A; Kalyan Suman (Indian Journal of Medical and Paediatric Oncology)
Endometrial adenocarcinoma is the third common malignancy of the female genital tract occurring most often in the postmenopausal age group. High tumor grade, advanced surgical stage, and lymphovascular space invasion are implicated as poor prognostic factors for dissemination of disease. We present an unusual case of endometrial adenocarcinoma in a premenopausal woman with simultaneous metastases in brain, liver, skin and skeletal system, within one month of completion of treatment. The role of adjuvant/concurrent chemotherapy in addition to radiotherapy in high risk cases is discussed along with the review of literature.